Climate Risk Management in Agriculture (CRMA) University Curriculum Validation Workshop - Grossi, Amanda; Dinku, Tufa; Hansen, James (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
A two-day curriculum validation workshop was implemented from May 24-25, 2022, in Adaama, Ethiopia by the International Research Institute for Climate and Society (IRI) of the Columbia Climate School. The workshop, which was organized as part of the World Bank’s Accelerating the Impact of CGIAR Climate Research for Africa (AICCRA) project and in close collaboration with the Adapting Agriculture to Climate Today, for Tomorrow (ACToday) Columbia World Project, brought together representatives from ten agricultural universities in Ethiopia and the Regional Universities Forum for Capacity Building in Agriculture (RUFORUM) to review and validate curriculum content for a new three-week postgraduate course on Climate Risk Management in Agriculture (CRMA).